LAW AGAINST VAGRANCY IN 19TH CENTURY COSTA RICA: AN INTERPRETATION FROM BELOW - Sánchez Lovell, Adriana (2016)
This article discusses the experiences of Costa Ricans workers in relation to labor justice in the period between 1821 and 1900. The vagrancy law emerged to solve much institutionalized much of the social problems of 21th century. The application of these laws was observed in two periods: the first decades of independence and the last decades of the nineteenth century. Theoretically I am inspired by the history from the bottom up, allowing you to see relations between workers and employers with the intermediation of the state courts. Methodologically I relied on case studies.